Developing Teaching Materials in Reading Aloud for Students in Grade V of State Elementary School - Batubara, Yusmaini Ayu; Harahap, Rosmawati; Kartolo, Rahmat; Sutikno (ITScience (Information Technology and Science), 2025)
Reading teaching materials look like a story-based book learning media, which are used to convey learning materials to motivate students in practicing their reading skills aloud. Reading teaching materials entitled